(untitled) (Indonesian Sports Justice Review, 2024)
Youth sports in Indonesia play a crucial role in shaping the athletic development of young people, yet unequal access to resources and opportunities across social and economic divides poses a significant challenge to achieving social justice in this sector. This paper examines the barriers faced by youth from marginalized communities—particularly those in rural areas or from lower socio-economic backgrounds—in accessing quality athletic development programs. Drawing on data from national and regional sports policies, interviews with community leaders, sports administrators, and youth athletes, the study assesses how existing programs and infrastructure fail to provide equitable opportunities for all young people. The paper further explores the role of the government, NGOs, and private sector in bridging these gaps and promoting a more inclusive youth sports ecosystem. Recommendations for ensuring equal access to sports opportunities include targeted investment in rural areas, building community-based sports facilities, and integrating social justice principles into sports policy frameworks.